Simulation Study and Analysis of Different Polymer Material In Injection Mould Process of Plastic Gear By Using Moldflow Adviser Software and Taguchi Method - Mohammad, Ahmad Zahiruddin; Rafai, Noor Hakim (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In this study, Moldflow Adviser software was used to explore the injection moulding process ability of polyamide, polyphenylene ether (PPE) and polycarbonate/acrylonitrile butadiene styrene blends (PC/ABS). By altering the process parameters, the impacts of the process conditions for three different polymeric materials were evaluated and compared. To achieve this objective, a plastic gear was designed and used as product part. Mould temperature, melt temperature, and injection pressure is the process parameter that focused in determining the best processing ability for three material. At the end, the cooling quality result of all three gears were actually the same based on the simulation. However, the comparison of sink mark between this products, gear that made from PPE has the lowest value compare to those polyamide and PC/ABS. Result analysis also show that warpage indicator for PPE material in Moldflow®, attained the lowest value which mean at the same time, the volumetric shrinkage also the smallest compare to polyamide and PC/ABS material. Then, Taguchi method was applied in this study to find the main effects, analysis of variance (ANOVA) and single-to-noise ratio (S/N ratio) using the results from simulation. Through this investigation, the optimum process parameters for injection moulding process can be acquired and the primary process parameters that affect the performance of the gear can be determined.